Parental involvement and family motivational climate from the parents' perception: cross-cultural validation of the CMF-P questionnaire - del Prado Morales, Mirtha; Alonso-Tapia, Jesús; Simón Rueda, Cecilia (Anales de Psicología / Annals of Psychology, 2021)
The purpose of this study is to design and evaluate how Cuban and Spanish population are validated through CMF/P-Q studies and to determine the differences in the CMF perception of the parents of both countries. Participants were 892 parents; from them, 400 Spanish and 492 Cubans. Among the most important results are: Both in Spain and in Cuba, the CMF / P-Q Questionnaire, supports the validity of the theoretical Model that underlying it. The help offered by parents as an example to their children and the structure of school work at home by parents are the most important factors in the definition of the CMF. The structure of the CMF in several indicators of the Model was moderated by the culture, distinguishing different ways of acting between Spanish and Cuban parents in an agreement of a motivating family climate.